Implementasi Lima Nilai Budaya Kerja di Kantor Kementerian Agama Kabupaten Banyumas - Thontowi, Zulkifli Syauqi; Qowim, Muhammad; Dardiri, Achmad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
Inequality in employee performance lie is background this paper. The implementation of the five work culture values ​​of the Office of the Ministry of Religion (Kemenag) ilat Banyumas Regency shows the enthusiasm of work that must exist to support good performance in the office. The application of the five values ​​of the Ministry of Culture work to make the performance of the State Civil Service (ASN) more competitive, effective, and energetic in service programs that are accessible and well implemented. The background of this study departs from the problem of ASN performance in the Banyumas Ministry of Religion which is rigid and lacks enthusiasm or effective and maximum work spirit. This research is a study that discusses less than maximum communication between ASN so it needs to improve communication professionalism, employee integration, balanced innovation, shared responsibility, and role models in the Banyumas Regency Ministry of Religion office.